The land before time VI the secret of saurus rock - Universal Cartoon Studios; Universal Studios Home Video (Firm) (Universal City, Calif. : Universal Home Video, 1998)
On the distant edge of the Great Valley stand mysterious Saurus Rock and twin baby Threehorns, Dinah and Dana have run away to find it. It's up to Littlefoot, Cera, Spike, Duck and Petrie to bring them back!
Hi-fi stereo; digitally recorded.
Rated G.
VHS.
Closed-captioned.
Keywords: Dinosaurs -- Juvenile drama; Video recordings for the hearing impaired; Animated films; Children's films